Вентильні індукторні генератори радіального збудження з суміщеними обмотками - Лущик, В'ячеслав Данилович (НТУ "ХПІ", 2014)
Описана конструкція та принцип дії індукторних генераторів з суміщеними обмотками. Приведено теоретичне обґрунтування переваг розглянутих генераторів. Наведені дані експериментальних досліджень генераторів з суміщеними обмотками і, для порівняння, генераторів, що серійно виготовляються.

The design and principle of operation of inductor generators with combined windings are described. The theoretical substantiation of advantages of considered generators is presented. The data of experimental investigations of generators with combined windings and, for comparison, generators, which are made in series are presented.
Valve induction generators of radial excitation with combined windings
Keywords: безконтактний електричний генератор; кондукція; експериментальний зразок; зубці статора; type of generators; combined winding; magnetic circuit; experimental research